FACTORS RELATING TO THE LEVEL OF PREGNANT WOMEN'S SATISFACTION USING ANC SERVICE - Devvy Apriani; Tiyas Kusumaningrum (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground: Independent Midwifery Practice is a health service provider that has a significant contribution in providing mother and child health services. One important indicator in service is satisfaction. There are still many pregnant women who are not satisfied with the ANC services provided. The purpose of the study was to analyze factors related to satisfaction of pregnant women in using ANC services. Method: Cross sectional, with purposive sampling technique. The number of samples were 89 pregnant women who visited PMB in August - September 2019. The independent variables were maternal characteristics (age, parity, education, occupation), service quality, service facilities, and access (financing and distance systems). The dependent variable was the level of satisfaction. Data analysis used Somers'd Test and contingency coefficients. Results: Factors related to satisfaction level were service quality, service facilities and financing system with a value of p<α< 0.05 and factors not related to satisfaction level were age, education, parity, occupation and distance with a value of p>α>0.05. Conclusion: Good service, good facilities and the financing system used tend to produce high levels of satisfaction.